Nurturing women-led agri-businesses: Unleashing the potential of women–women networks - Puskur, Ranjitha; Singaraju, Niyati; Muchiru, Caroline; Dido, Sabdiyo (CGIAR GENDER Impact Platform, 2023)
VALUE4HER is a continental initiative of the Alliance for Green Revolution in Africa (AGRA) aimed at strengthening women’s agribusiness enterprises and enhancing voice and advocacy across Africa. The initiative aims to increase the performance of women entrepreneurs through access to markets and trade, access to finance and investments, learning, networking, and global advocacy aimed at addressing some of the key barriers to women’s business growth and market participation in agriculture. In 2021, the initiative provided innovation grants to 20 SMEs from nine African countries to catalyze market and learning networks and mentorship among women-led businesses. Each of these entrepreneurs connected with 20 micro and nano women entrepreneurs and collaborated with them and mentored them. This presentation highlights the short-term outcomes of this grant including the changes in financial, production and marketing management made by the women entrepreneurs; the enterprise characteristics like revenues and profit margins; and their attitudes and perceptions toward business growth and the role of the network and mentorship in influencing these changes. It also highlights some challenges the entrepreneurs face to grow their businesses, including their limited access to financial and risk management products, time poverty, limited mobility, and agency. The presentation also identifies areas that need more research to inform similar efforts at a larger scale, and to ensure that they responsibly contribute to women’s economic empowerment through entrepreneurship.